METHODICAL APPROACHES TO FORMING INNOVATIVE PROJECT AND ENTERPRISE MANAGEMENT ORGANIZATIONAL STRUCTURES - A. O. Baklanov; N. I. Didenko; K. I. Lugovtsev; I. M. Yagudin (Модернизация, инновация, развитие)
The following principles are discussed as methodical bases of the choice of innovative project and enterprise management organizationalstructures: hierarchism, bureaucratization, adhocratie, tent organization, lean business engineering, rational organization, amorphousorganization, teaching organization. Conditions that complicate industrial and technological processes influence enterprise managementprocess dynamics. The variety of existing types of organizational structures is determined by industrial, economic, psychological and social conditions.